Optical and photoluminescent properties of Ag/Al₂O₃ nanocomposite films obtained by pulsed laser deposition - Manoilov, E.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The method of pulsed laser deposition in vacuum from forward and backward particle flows from an erosion torch was used to prepare silver films and Ag/Al₂O₃ nanocomposite films. Measured were transmission and time-resolved photoluminescence spectra. The authors studied the influence of conditions for film formation on their optical and photoluminescent properties. For the first time, there observed was luminescence with quantum energy 1.6 eV and relaxation times up to several microseconds.